Complete Genome Sequences of Six Measles Virus Strains - Phan, My V. T. (Genome Announc, 2018)
Genetic characterization of wild-type measles virus (MV) strains is a critical component of measles surveillance and molecular epidemiology. We have obtained complete genome sequences of six MV strains belonging to different genotypes, using random-primed next generation sequencing.